Sleep, screen time, and family meal frequency in preschool children: A pilot study. Issue 8 (August 2020) - Hayes, Katey; Williams, Susan G.; Fruh, Sharon; Graves, Rebecca J.; Minchew, Leigh A.; Hall, Heather R.
Abstract : Abstract: This exploratory pilot study identified the prevalence and perceptions of three healthy habits in preschool-age children by surveying their parents/caregivers. Researchers examined children's hours of sleep, screen time, and number of family meals per week. Abstract : This exploratory pilot study identified the prevalence and perceptions of three healthy habits in preschool-age children by surveying their parents/caregivers. Researchers examined children's hours of sleep, screen time, and number of family meals per week.